Investigation of jumping pulsed electrical discharge for plasma chemistry application - Berezina, G.P.; Bunchikov, Ju.V.; Mirny, V.I.; Onishchenko, I.N.; Us, V.S. (Вопросы атомной науки и техники, 2002)
The behaviour of the pulsed discharge at atmospheric pressure between multiple needles- plane electrode has been investigated. This type of discharge has been used in our experiments as a suitable tool for plasma chemistry of COx, NOx and SOx, i.e. for effective decomposition of these radicals. The main advantage of it concludes to a phenomenon of spark jumping from one needle to another over whole volume of treated gas. The behaviour of the pulsed discharge of such type has been studied with use of the optical registration method of discharge for each needle.